(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
The aim of the article is determined by the very conceptual meaning of the concept of "time" in the general context of the world picture. The study involves the consideration of the Japanese tradition of time perception for many centuries and is naturally connected with religion, philosophy and economic way of life in Japan throughout the history of the country.